(untitled) (Ukrainian Journal of Ophthalmology, 2026)
The aim of our study was to analyze the effectiveness of vitrectomy and vitrectomy with scleral buckling in patients with a high risk of proliferative vitreoretinopathy. Material and Methods: Of the 367 patients (394 eyes) who applied in 2011-2014, in the National Center for Ophthalmology named after acad. Zarifa Aliyeva with diagnosis of primary rhegmatogenous retinal detachment (RRD) we selected 217 patients (231 eyes) with a high risk of proliferative vitreoretinopathy. The patients were considered to be of a high risk of proliferative vitreoretinopathy (PVR) development if they had RRD in three or more quadrants, more than one hour retinal breaks, pre-operative PRV, vitreous hemorrhage, aphakia/ pseudophakia, choroidal detachment. Vitrectomy and vitrectomy with scleral buckling were performed in 133 eyes (57.6% of cases) and 98 eyes (42.4% of cases), respectively. Results: The primary anatomical success of the surgery was noted in 71.4 and 70.4% of cases after vitrectomy and vitrectomy with scleral buckling, respectively, p=0.866. The final anatomical success was observed in 88.7 and 92.9%, after vitrectomy and vitrectomy with scleral buckling, respectively, p=0.290. In pseudophakia the primary anatomical effect was noted in 80.6 and 53.3% of cases after vitrectomy and vitrectomy with scleral buckling, respectively, p=0.054. In RRD associated with lowere breaks, the final anatomic success was observed in 85% and 96.2% of cases after vitrectomy and vitrectomy with scleral buckling, respectively, p=0.05. Conclusion: In rhegmatogenous retinal detachments in patients with a high risk of developing proliferative vitreoretinopathy, vitrectomy is more effective in pseudophakic patients and vitrectomy with scleral buckling is more effective in retinal detachments caused by inferior breaks.